2004
DOI: 10.1021/jp037735l
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of Butyrophenone:  Combined Complete-Active-Space Self-Consistent Field and Density Functional Theory Study of Norrish Type I and II Reactions

Abstract: The complete-active-space self-consistent field (CASSCF) and density functional theory (DFT) approaches have been used to study the mechanistic details of Norrish type I and II reactions of aromatic carbonyl compounds, with butyrophenone (PhCOCH 2 CH 2 CH 3 ) as a representative. A minimum energy crossing point was found to exist among three potential energy surfaces (S 1 , T 1 , and T 2 ), and the three-surface crossing allows the T 2 state to act as a relay that enables the intersystem crossing (ISC) from S … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
47
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 60 publications
3
47
2
Order By: Relevance
“…We have applied the CASSCF method to determine the dark transient structures involved in radiationless processes of acetophenone and the related aromatic carbonyl compounds. [29][30][31][32] The electronic and geometric structures predicted for the dark states are in a good agreement with those determined by ultrafast electron diffraction experiments. [11][12][13] Intersection structures of different electronic states that provide a very efficient "funnel" for the IC and ISC processes can be determined with high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…We have applied the CASSCF method to determine the dark transient structures involved in radiationless processes of acetophenone and the related aromatic carbonyl compounds. [29][30][31][32] The electronic and geometric structures predicted for the dark states are in a good agreement with those determined by ultrafast electron diffraction experiments. [11][12][13] Intersection structures of different electronic states that provide a very efficient "funnel" for the IC and ISC processes can be determined with high-level ab initio calculations.…”
Section: Introductionsupporting
confidence: 77%
“…[29][30][31][32] The CASSCF-optimized bond parameters for these carbonyl molecules in the five lowest electronic states have been reported in the previous calculations. [29][30][31][32] For comparison, the CsC and CsO bond lengths for benzaldehyde and acetophenone in the T 2 state are listed in Table 1, where the available experimental values are also given. In the ground state, the aromatic ring was predicted to be almost a regular hexagon with the CsCsC angle in the range of 119.8°-120.3°and the largest difference of 0.012 Å in the ring CsC bond length.…”
Section: Equilibrium Geometriesmentioning
confidence: 99%
“…The progression of the C-O bond stretch fits well with the T K of 1 having an (n,p*) configuration. [31][32][33][34] The calculated energies of the T K s of 1A, 1B, and 1C are~8 kcal/mol (1 cal = 4.184 J) lower than the measured value for the analogous benzophenone. However, we have previously shown that DFT calculations underestimate the energy of triplet ketones with an (n,p*) configuration.…”
Section: Calculationscontrasting
confidence: 56%
“…Theoretical calculations are useful method to estimating thermodynamic properties of biradical intermediates if direct detection of biradical intermediates is difficult. 13,14 Fang and coworkers have investigated the Norrish type I and II reaction of butyrophenone using complete-active-space self-consistent field (CASSCF) theory and density functional theory (DFT). The authors calculated energies and lifetimes of reaction intermediates including 1,4-biradical intermediate.…”
mentioning
confidence: 99%
“…The authors calculated energies and lifetimes of reaction intermediates including 1,4-biradical intermediate. 13 In this paper, we have performed quantum chemical calculation using density fuctional theory to optimize geometries and energies of the each chemical species involved in the photochemical reaction of o-ethoxybenzophenone (RH) and o-2,2,2-trifluoroethoxybenzophenone (RF) using Gaussian 03 package of programs 15 based on the previous reports that B3LYP method has demonstrated efficient reproducibility of the observed structures, barrier heights, and transition energies of biradical intermediates. [16][17][18][19][20] The aim of this study is to understand final branching ratios of the diastereomers shown in Figure 1 in the view of energy aspect.…”
mentioning
confidence: 99%